2023
DOI: 10.1021/acs.molpharmaceut.3c00016
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Food and a Proton-Pump Inhibitor on the Absorption of Encorafenib: An In VivoIn VitroIn Silico Approach

Abstract: Encorafenib is a kinase inhibitor indicated for the treatment of patients with BRAF mutant melanoma and BRAF mutant metastatic colorectal cancer. To understand the effect of food and coadministration with a proton-pump inhibitor (PPI), in vitro, in vivo, and in silico data were generated to optimize the clinical dose, evaluate safety, and better understand the oral absorption process under these conditions. Study 1 evaluated the effect of food on the plasma pharmacokinetics, safety, and tolerability after a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…After that, the male animals were selected for subsequent studies. In addition, all the pharmacokinetic studies were executed in the overnight fasted condition (∼10 h) to avoid any variation due to the fed state, as it is reported that there might be a lower exposure in the presence of food . To investigate the pharmacokinetics of EIDD-1931 under any disease state, we first induced the particular disease state and confirmed by disease-specific marker(s) supported by histopathological findings wherever required.…”
Section: Discussionmentioning
confidence: 99%
“…After that, the male animals were selected for subsequent studies. In addition, all the pharmacokinetic studies were executed in the overnight fasted condition (∼10 h) to avoid any variation due to the fed state, as it is reported that there might be a lower exposure in the presence of food . To investigate the pharmacokinetics of EIDD-1931 under any disease state, we first induced the particular disease state and confirmed by disease-specific marker(s) supported by histopathological findings wherever required.…”
Section: Discussionmentioning
confidence: 99%
“…This was likely attributed to the limited efficacy of a liquid diet in delaying gastric emptying and reducing small intestinal motility. Meanwhile, food may alter lapatinib bioavailability by changing the gastrointestinal pH, increasing splanchnic blood flow, affecting metabolism, and many other factors ( Huh et al, 2023 ; Piscitelli et al, 2023 ; Vertzoni et al, 2019 ). In the rat model, TPF-T had minimal influence on the lapatinib pharmacokinetics probably because rats had higher bile flow.…”
Section: Discussionmentioning
confidence: 99%
“…It also shows the expanded space of oral small molecule drug delivery including modeling and artificial intelligence. In the industrial setting these computational approaches are used both in the discovery space to select the right candidates but also as part of formulation development to model absorption, formulation processes, and degradation pathways or as part of process development.…”
mentioning
confidence: 99%